Target sequence data shed new light on the infrafamilial classification of Araceae - Anna, L. Haigh; Marc, Gibernau; Olivier, Maurin; Paul, Bailey; Mónica M., Carlsen; Alistair, Hay; Kevin, Leempoel; Catherine, McGinnie; Simon, Mayo; Wong, Sin Yeng; Alejandro, Zuluaga; Alexandre R., Zuntini; et al. (Botanical Society of America, 2022)
Recent phylogenetic studies of the Araceae have confirmed the position of the duckweeds nested within the aroids, and the monophyly of a clade containing all the unisexual flowered aroids plus the bisexual-flowered Calla palustris. The main objective of this work was to better resolve the deep phylogenetic relationships among the main lineages within the family, particularly the relationships between the eight currently recognized subfamilies. We also aimed to confirm the phylogenetic position of the enigmatic genus Calla in relation to the long-debated evolutionary transition between bisexual and unisexual flowers in the family.